IMPROVING COMPETENCIES OF PACKET C TUTORS THROUGH G SUITE FOR EDUCATION TRAINING (Case Study at PKBM Cahaya Kahuripan Bangsa Lembang) - Lince Sari Dianawati Leatemia; Erni Furwanti; Enceng Mulyana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This research aims to answer how G Suite for Education training might contribute toward competency increase of PKBM Cahaya Kahuripan Bangsa’s Packet C tutors. The goal is to describe data about how the training is planned, how the training proceeds, and how the results of the training are. The qualitative approach is implemented through narrative descriptive methods. Data is gathered through observation, interview and document study. The subjects of this research include PKBM Cahaya Kahuripan Bangsa tutors as participants of the training, the instructor and the organizing committee. Gathered data shows that in the planning phase, instructor recruitment emphasizes heavily on the competencies of the instructor candidate. The lesson plans and curriculum devised by the instructor is further adapted to meet the competencies as described by Google and stresses on product. On the process, the participants explore more time to try the products on their own. The participants are happy and feeling beneficial, yet they feel the time is too sparse. The benefits they feel, in general, includes the ability to understand and use new applications usable in classroom learning contexts. The results show that the training improves the tutors’ competencies.